Total quality management of Bukidnon State University - Vasallo, Josefina L. (Bukidnon State University Library Research Journal, 2008)
Total quality management is the integration of all functions and processes within an organization in order to achieve continuous improvement of the quality of services. The goal is client satisfaction. TQM is based on a number of ideas. It means thinking about quality in terms of all functions of the institution and is a start-to-finish process that integrates interrelated functions at all levels. It is a systems approach that considers every interaction between the various elements of the organization, Thus, the overall effectiveness of the system is higher than the sum of the individual outputs from the subsystems. Basic to the concept of TQM is the notion that quality is essential in all functions. This is justified by reason of organization synergism: the need to provide quality output to internal as well as external customers and the facilitation of a quality culture and value system of the organization. Nowhere is the philosophy of “customer is king”, more prevalent than TQM. Customers are both external (including channels) and internal (including staff functions) to the business. The categories for total quality management were patterned from Deming (1954), Juran and Crosby (1985). Deming sees that the problem of quality is due mainly to management’s failure to plan ahead. The emphasis on prevention rather than cure is his unique contribution to an understanding of how to assure the improvement of quality. Crosby’s name is associated with two powerful ideas: quality is free and errors, failures, waste and delay, all the “unequality things” can be totally eliminated. Crosby’s model is pure prevention model. This study used the following categories: 1. Access which analyzed the point of contract; 2. Services for the students an advice and guidance; 3. Leadership which focus on Bukidnon State University administrators leadership and values; 4. Physical environment and resources, assessment on the buildings, classroom, workshop, health and safety, and resources control and allocation; 5. Effective learning, an analysis of the appropriateness of learning methods, appropriateness of the portfolio of courses, monitoring and evaluation; 6. Students matter and satisfaction; 7. Staff’s attitude motivation, teamwork, staff development and facilities; 8. External relations; 9. Organization’s strategic planning, organizational culture, and communication; and 10. Standards, on soft, hard and correct application of standards. The respondents would assess Bukidnon State University total quality management based on the above mentioned categories with the following relations: excellent, very satisfactory, satisfactorily, fair, and poor. The student’s were chosen as the respondents because they are the prime client of this institution. The paradigm of TQM applies to all enterprises, government agencies and departments. Thus, this study tried to analyze the Total Quality Management of Bukidnon State University. The student’s assessment of Bukidnon State University TQM as the based line data of this study. TQM, a Japanese-inspired approach to improved organizational performance, is a way of life for an organization as a whole, committed to total customer satisfaction through a continuous process of improvement and the contribution and involvement of people. The successful organization should as a matter of policy be constantly seeking opportunities to improve the quality of its product and/or services and processes. TQM emphasizes the importance of people as the key to quality. Human resource management and quality management are converging to give total quality. It is lack of communication and awareness that causes failures and costs. There has been too much reliance on systems. Although systems are necessary, they are only as effective as the people who design them. Changes in the traditional organization structure and the increasing importance of effective work groups emphasize team-based management as an essential element. With the aforementioned contentions, the researchers was prompted to conduct a study on the total quality management of Bukidnon State University, Malaybalay City.